Management assistants for e-commerce - a new training occupation from 1 August 2018 - Zimmermann, Manfred [Verfasser]; Spillner, Gunther [Verfasser] (My University, 2019)
"With the boom in the online trading of goods and ser- vices, the significance and scope of e-commerce is growing across all industries. New areas of activity and new organisational and business models are emerging. To meet the growing need for skilled workers in e-commerce a new commercial occupation has been created. The article highlights the background to the revision of the training regulations and describes the occupational profile." (Author's abstract ; BIBB-Doku)
Kaufleute im E-Commerce – Ein neuer Ausbildungsberuf ab 1. August 2018
Keywords: S 6.4.1 Kaufleute; Kaufmännischer Beruf; Kaufmann im E-Commerce; Neuordnung der Ausbildungsberufe